2004
DOI: 10.1259/bjr/22642890
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the characteristic curve on the clinical image quality of lumbar spine and chest radiographs

Abstract: The "European Guidelines on Quality Criteria for Diagnostic Radiographic Images" do not address the choice of the film characteristic (H&D) curve, which is an important parameter for the description of a radiographic screen-film system. The image contrast of clinical lumbar spine and chest radiographs was altered by digital image processing techniques, simulating images with different H&D curves, both steeper and flatter than the original. The manipulated images were printed on film for evaluation. Seven exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…From this, it is doubtful that the fulfilment of the investigated quality criteria for the visualisation of normal structures in a VGA experiment is sufficient for accurate detection of microcalcifications. Similar results, but for a different clinical task, were found in the Tingberg et al study [29]: they investigated the correlation between a VGA experiment and the objective ROC study for the detection of lumbar lesions, and also found no agreement between the two methods.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…From this, it is doubtful that the fulfilment of the investigated quality criteria for the visualisation of normal structures in a VGA experiment is sufficient for accurate detection of microcalcifications. Similar results, but for a different clinical task, were found in the Tingberg et al study [29]: they investigated the correlation between a VGA experiment and the objective ROC study for the detection of lumbar lesions, and also found no agreement between the two methods.…”
Section: Discussionsupporting
confidence: 76%
“…Correlation between VGA experiments and more objective ROC studies has previously been investigated, but the results of the few published studies are contradictory [28][29][30]. Pilgram et al [28] found a strong correlation between diagnostic performance and the subjective evaluation of image quality on the diagnosis of craniosynostosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The monitors were calibrated to national standards [27]. Image criteria were based on the Council of European Communities (CEC) Quality Criteria [28], slightly revised to reflect modern diagnostic requirements and experiences of other groups [29][30][31][32][33]. Test images (50, 60, 70, 81, 90, 109, 125, 133, 141 and 150 kV) were scored against a reference image at a tube voltage of 102 kV, with negative and positive scores indicating inferior and superior image quality, respectively (tube voltages stated here were those available on the Philips radiographic system).…”
Section: Scoring Of Simulated Chest Images (Derived From Previous Work)mentioning
confidence: 99%